17β-Estradiol signaling in skeletal muscle cells and its relationship to apoptosis - Boland, Ricardo Leopoldo (2008)
17β-Estradiol exerts an antiapoptotic action in skeletal muscle cells through extranuclear ERα and β. This protective action, mainly involves a non-genomic mechanism of ERK1/2 and PI3K/Akt activation and BAD phosphorylation. ERβ plays a major role in the inhibition of apoptosis by 17β-estradiol at the level of mitochondria, whereas ERα and ERβ mediate the activation of Akt to the same extent, suggesting differential involvement of ER isoforms depending on the step of the apoptotic/survival pathway involved. The myopathies associated to estrogen deficit states may be related to the mechanisms by which estrogen regulates apoptosis.